DETERMINAN TINGKAT KEMISKINAN DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Fairizta, Yunia Arien; suharno, suharno; anwar, nurul (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.12.TAHUN 2020DO - 10.24843/EEB.2020.v09.i12.p04, 2020)
The percentage of poor people in the Special Region of Yogyakarta Provinceis higher when compared to other provinces in Java Island. In addition, the number of visits by foreign and domestic tourists in the Special Region of Yogyakarta Province is quite significant. This study aims to analyze the effect of tourism sector, life expectancy, and the average length of schooling on poverty in the Special Region of Yogyakarta Province. The research method uses multiple linear regression with a panel data approach. The results showed that of tourism sector, life expectancy, and average length of schooling had a negative and significant effect on poverty in the Special Region of Yogyakarta Province  in 2000-2019. These findings recommend the need for the development of the tourism sector that involves the participation of local communities. In addition, development of equitable education and health infrastructure to improve the quality of education and public health in the Special Region of Yogyakarta Province.   Keywords : Poverty, Tourism, life expectancy, education